(untitled) (Journal of Bio-Science, 2026)
The carbon dioxide (CO₂) sequestration efficiency of five selected tree species- Swietenia macrophylla (Mahogany), Acacia auriculiformis (Akashmoni), Tectona grandis (Shegun), Ficus benghalensis (Banyan tree) and Borassus flabellifer (Tal palm) was estimated using a non-destructive method. Tree height and trunk diameter were measured at breast height (4 ft) and above breast height (6 ft) to assess CO₂ sequestration potential. At a trunk height of 4 ft, the highest CO₂ sequestration was recorded in F. benghalensis, with an estimated 198,070.59 kg, whereas the lowest was observed in B. flabellifer, with 13,425.46 kg. Similarly, at 6 ft trunk height, F. benghalensis exhibited the maximum CO₂ sequestration (233,812.999 kg), while B. flabellifer showed the minimum (9,992.96 kg). These results indicate that F. benghalensis is the most effective species for CO₂ sequestration among the studied trees, likely due to its large trunk diameter, extensive biomass and wide canopy structure, which contribute to greater carbon storage capacity. J. Bio-Sci. 34(1): 125-129, 2026